2015
DOI: 10.1109/lsp.2015.2481720
|View full text |Cite
|
Sign up to set email alerts
|

A Zero-Crossing Rate Property of Power Complementary Analysis Filterbank Outputs

Abstract: We establish zero-crossing rate (ZCR) relations between the input and the subbands of a maximally decimated -channel power complementary analysis filterbank when the input is a stationary Gaussian process. The ZCR at lag is defined as the number of sign changes between the samples of a sequence and its -sample shifted version, normalized by the sequence length. We derive the relationship between the ZCR of the Gaussian process at lags that are integer multiples of and the subband ZCRs. Based on this result, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The ZCR is defined as the number of sign changes within a time series signal, specifically referring to the number of times the signal crosses the zero-level reference. Based on the definition, thus the ZCR can provide information about the number of zero-crossings present in a specific time period [40]. In particular, if the number of the zero-crossings is large, it implies that the given signal is undergoing rapid changes in that time period.…”
Section: Mixed Feature Vectors Constructionmentioning
confidence: 99%
“…The ZCR is defined as the number of sign changes within a time series signal, specifically referring to the number of times the signal crosses the zero-level reference. Based on the definition, thus the ZCR can provide information about the number of zero-crossings present in a specific time period [40]. In particular, if the number of the zero-crossings is large, it implies that the given signal is undergoing rapid changes in that time period.…”
Section: Mixed Feature Vectors Constructionmentioning
confidence: 99%
“…In conjunction with an ordinary k-means algorithm, ZCRs allowed the identification of quasi-periodic patterns that are key for their task, attaining 96.10% accuracy with 110 music clips and 140 speech files. Reciprocally, the authors of article [19] showed a ZCR-based estimator that works better than the sample autocorrelation method to analyse stationary Gaussian processes. Their work was successfully developed on the basis of a mathematical analysis of random noise.…”
Section: A Review On Zcrs and Their Applicationsmentioning
confidence: 99%